Application of Criminal Sanctions Against Drug Crimes in Cirebon Jurisdiction - Andri Winjaya Laksana; Ardiman, ‎ (KnE Social Sciences, 2025)
Recently, narcotics and illegal drugs crimes have become transnational in nature, carried out with high modus operandi and sophisticated technology. Law enforcement officers are expected to be able to prevent and overcome these crimes in order to improve the morality and quality of human resources in Indonesia, especially for the next generation. This study aims to determine the application of criminal sanctions against narcotics crime perpetrators in the Cirebon jurisdiction. It uses a normative legal approach and normative legal research method. The legal research is conducted by examining library materials or secondary data. The research specification used is analytical descriptive, used to to analyze and explain legal problems related to objects with a comprehensive and systematic description of everything related to the application of criminal sanctions against narcotics crime perpetrators. This implementation is carried out based on Law Number 35 of 2009 concerning Narcotics. The sanctions given to perpetrators of narcotics crimes are imprisonment for 4 years and a fine of IDR. 800,000,000 (eight hundred million rupiah). Obstacles that arise in the implementation of criminal sanctions against narcotics crime offenders are certainly inseparable from the law enforcement process itself. A crucial problem in law enforcement against narcotics crimes is the difficulty of tracking the whereabouts of narcotics criminals.